PENGARUH KEPEMIMPINAN DIGITAL KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP KUALITAS PEMBELAJARAN PADA SEKOLAH DASAR DI KECAMATAN LABAKKANG - Asmaul Husna; Arismunandar; Ansar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was aims to analyze the influence of school principals’ digital leadership and teachers’ work motivation on the quality of education in elementary schools in Labakkang District. The method used in this study was a quantitative approach with a causal-associative (ex post facto) design. The sampling technique employed was cluster random sampling; the sample consisted of 19 schools with 178 participants. Data was collected through questionnaires, documentation, and observation, then analyzed used descriptive and inferential statistics with multiple linear regression techniques. The data was analyzed used multiple linear regression to determine the effect of each independent variable on the dependent variable. In presenting the data, SPSS version 25.0 was used to process the data according to existing formulas. The results of this study indicate that the principal’s digital leadership falls into the “good” category, while teachers’ work motivation falls into the “poor” category. Partially, the principal’s digital leadership has a positive and significant effect on the quality of learning. Teachers’ work motivation was also found to have a positive and significant effect on the quality of learning. Simultaneously, the principal’s digital leadership and teachers’ work motivation has a significant effect on the quality of learning. The result of the coefficient of determination (adjusted R-squared) is 0.483, which indicates that 48.3% of the quality of learning is influenced by the principal’s digital leadership and teachers’ work motivation at elementary schools in Labakkang Subdistrict. It can be concluded that the principal’s digital leadership and teachers’ work motivation play a crucial role in improving the quality of learning at the school. Therefore, it is recommended that schools, principals, teachers, and education policymakers pay special attention to the implementation of the principal’s digital leadership and teachers’ work motivation to enhance the quality of learning at the school.